Traditional Vs Modern: Effect of Cultural Dimensions on Tourist Buying Intentions in the Context of Tourism Marketing - Ahmad Alsaggaf, Mohammed (British Journal of Marketing Studies, 2024)
This empirical study delves into the intersection of cultural dimensions and tourist revisit intentions within the green restaurant sector. Leveraging co-variance-based Structural Equation Modelling (CB-SEM) to test hypotheses, the research scrutinizes data collected from 326 tourists who participated in an online survey after visiting green restaurants. The analysis aims to uncover how various cultural dimensional factors—such as collectivism, power distance, and uncertainty avoidance—play a crucial role in shaping tourists’ decisions to revisit environmentally friendly dining establishments. Preliminary findings suggest that cultural dimensions significantly influence revisit intentions, with particular nuances that could inform targeted marketing strategies for green restaurants aiming to enhance customer loyalty and promote sustainable dining practices. This study not only contributes to the broader understanding of consumer behaviour in the context of sustainable tourism but also offers practical insights for restaurant managers and marketers seeking to align their offerings with the cultural preferences of their clientele.